Investigation of Experimental and In Silico Physicochemical Propertiesof Thiazole-Pyridinium Anti-Acetylcholinesterase Derivatives withPotential Anti-Alzheimer's Activity - Golaleh Ghotbi; Maryam Hamzeh-Mivehroud; Arezou Taghvimi; Soodabeh Davaran; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2021)
Background: Physicochemical properties play important role in fundamental issues likeabsorption and distribution of pharmaceuticals to the target tissue. This is particularly importantfor drugs acting in central nervous system (CNS). In this study, physicochemical properties ofpreviously synthesized thiazole-pyridinium derivatives with anti-acetylcholinesterase activityand possible anti-Alzheimer effect were studied. Methods: Partition coefficient (n-octanol/water) and chromatographic Rf values for the studiedcompounds were determined using shake flask and high performance thin layer chromatography(HPTLC) methods, respectively. Different druglikeness properties of the compounds were alsocalculated using available software and web-servers. Results: The experimentally determined logarithm of partition coefficients (log P) for thestudied compounds were in the range of -1.00 to -0.38. The Rf values for the studied compoundsunder the applied chromatographic condition ranged between 0.38 to 0.58. Moreover, calculatedphysicochemical properties, and druglikeness scores of the studied thiazole-pyridiniumderivatives and matching piperidine analogues were predicted. Furthermore, some ADMETfeatures of studied compounds like toxicity and metabolism by CYP450 (2C9, 2D6, 3A4, 1A2and 2C19) enzymes were predicted. Conclusion: The ranges of experimental and calculated LogP values for the studied thiazolepyridinumswere close. However, the determined Rf values showed relatively better correlationto the predicted LogP values indicating the suitability of used chromatographic method forcomparing the lipophilicity of the positively charged pyridinium derivatives. The studiedcompounds were predicted to pass GI membrane and reach the CNS where they can exerttheir effects. In silico studies indicate that the piperidine counterparts of the studied thiazolepyridiniumsmay represent anti-Alzheimer agents with improved druglikeness properties.